THE INFLUENCE OF ISOPROPYL ALCOHOL CONCENTRATION ON THE CHANGE OF PHASE BEHAVIOR IN THE MIXTURE OF OIL - SURFACTANT - ISO PROPYL ALCOHOLFORMATION WATER - Nuraini Nuraini (Scientific Contributions Oil and Gas, 2005)
Surfactant is surface active agent chemical that has two types of properties; lyophobic (like water) and hydrophobic (like oil). One of enhanced oil recovery methods that is used to improve oil recovery factor, is surfactant flooding. Oil and water are two separated phases and have high interfacial tension value (around 30-40 dyne/cm). Addition of surfactant solution at certain concentration into the mixture of oil-surfactant-formation water will change the phase behavior. In this case, four types possibilities of emulsion formed, these are: • Upper phase; Middle phase (microemulsion); Lower phase; Macroemulsion. According to Prince, L.M (Theory and Practice of Microemulsions), change of phase behavior in the oil-surfactant-formation water mixture is influenced by several factors, one of them is concentration of alcohol. The main focus of this research is to study influence of isopropyl alcohol (IPA) concentration on phase behavior in the oil-surfactant-IPA-formation water mixture.Concentration Behavior Oil - Surfactant - Iso